Organolithium-induced alkylative ring opening of aziridines: synthesis of unsaturated amino alcohols and ethers. - Hodgson, D; Stefane, B; Miles, T; Witherington, J (2006)
Organolithium-induced alkylative ring opening of N-sulfonyl-protected aziridinyl ethers is described. The reactions were efficiently carried out with a variety of organolithiums, providing a promising new strategy to unsaturated amino alcohols and ethers. Cis- and trans-1,4-dimethoxybut-2-ene-derived aziridines were prepared, and their propensity to undergo organolithium- induced alkylative desymmetrization is detailed. Use of a single enantiomer of the latter aziridine provides a route to enantiopure unsaturated amino ethers.